Nanocompósitos de óxidos de ferro e pontos de carbono e suas aplicações em processos oxidativos avançados - Therese Cibaka Ebambi (2019)
Photocatalysis reaction are promoted by the UV/Vis irradiation and catalyzed by semiconductors that undergo excitation of an electron from the valence band to the conduction band. The pair of electron (excited in the conduction band) and hole (in the valence band) gives the semiconductor its photocatalytic activity. The efficiency ofphotocatalysis depends on how slow the decay of the excited electron to the original valence band, ie the electron recombination hole. Iron (III) oxides are potential photocatalysts because of their band gap ofapproximately 2 eV, ideally this value allows the use of radiation in the UV / visible region. However, iron oxides present a rapid recombination of the electron-hole pair. Most of the time, the iron oxides are modified in order to inhibit this recombination by heterijunction or favour the Fe3+ reduction to Fe2+ via metal-ligand transference. This work presents compositesof iron oxides with carbon dots. Three iron oxide species were synthesized: hematite, akaganeite and ferrihydrite. With each of these species, the composite iron oxide / citric acid based carbon dots (PC-AC / EDA) and the composite iron oxide / castor oil based carbondots(PC-RIC) were synthesized. In total, 6 composites were formed. These composites were characterized and a modification of particle size and the valence band energy value compared to the initial iron oxides. In addition, the photocatalytic activity of the composites was testedin the discoloration of methylene blue by photofenton. For all iron oxides, except for ferrihydrite, the addition of PCs to the structure of ironoxides improved the catalytic activity in photofenton. The akaganeite / PC-AC / EDA composite showed the best performance in photofenton. After only 10 minutes, the akaganeite / PC-AC / EDA composite allowed the complete degradation and discoloration of the methylene blue dye while pure akaganeite, under the same conditions, did not promote anyapparent discoloration. The presence of PC-AC / EDA in the akaganeite matrix acted as a stabilizing agent and conferred the akaganeite smaller particules size and a greater structural stability. Thus, the introduction of carbon dots into the iron oxide structure is a promising solution to allow the effective use of these oxides as a photocatalyst.